1999
DOI: 10.1001/jama.282.6.561
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF2, a TNF-α Promoter Polymorphism, With Septic Shock Susceptibility and Mortality

Abstract: The TNF2 allele is strongly associated with susceptibility to septic shock and death due to septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
355
6
20

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 699 publications
(405 citation statements)
references
References 50 publications
21
355
6
20
Order By: Relevance
“…This contrasts with studies linking severe sepsis outcome and LTA þ 252 genotype, 36,37 and the TNF À308 polymorphism with outcome in septic shock and meningococcal disease. 39,40 However, our findings concur with those of another study in which it was reported that there is no association between the TNF À308 polymorphism and severe sepsis. 41 The discrepancy between the findings in these different studies could be a result of differing disease severity scoring methods, differing lengths of time before hospitalisation and treatment, and variations in the rapidity and type of treatment, all factors that may vary in different geographical areas.…”
Section: Discussionsupporting
confidence: 91%
“…This contrasts with studies linking severe sepsis outcome and LTA þ 252 genotype, 36,37 and the TNF À308 polymorphism with outcome in septic shock and meningococcal disease. 39,40 However, our findings concur with those of another study in which it was reported that there is no association between the TNF À308 polymorphism and severe sepsis. 41 The discrepancy between the findings in these different studies could be a result of differing disease severity scoring methods, differing lengths of time before hospitalisation and treatment, and variations in the rapidity and type of treatment, all factors that may vary in different geographical areas.…”
Section: Discussionsupporting
confidence: 91%
“…Sepsis patients may represent the tail end of the distributions for TNF production, making this population an excellent target for well-matched casecontrol studies. While an early study of the role of the À308 SNP 118 in a group of 80 patients with septic shock found no association with disease incidence, a subsequent French study 119 involving 89 patients found that the À308 A allele was both more common in patients than controls (39 vs 18%, P ¼ 0.002), and was also more frequent among those who died (54 vs 24%, P ¼ 0.008). After correction for confounders, carriage of the TNF À308 A allele was shown to lead to a 3.7-fold increase risk of death.…”
Section: Leprosymentioning
confidence: 94%
“…Examples of conflicting observations have primarily concerned single-nucleotide polymorphisms (SNPs) in genes involved in the innate immune response, such as tumor necrosis factor-alpha (TNF-a), lipopolysaccharide (LPS) binding protein (LBP) and CD14. [3][4][5][6] LPS is a major component of the outer wall of Gram negative bacteria, serving as the key ligand for immune cell recognition and activation in response to infection. Innate immune cells, such as macrophages and monocytes, recognize endotoxin by a specific receptor complex, which contains CD14, LPS, LBP, and Toll-like receptor-4 (TLR4).…”
Section: Introductionmentioning
confidence: 99%